Ball-Mill Assisted Green One-Pot Synthesis of ZnO/Graphene Nanocomposite for Selective Electrochemical Sensing of aquatic pollutant 4-nitrophenol - P, Kavya; S, Soorya V; Narayanan, Binitha N (Teknomekanik, 2021)
ZnO, having good transparency, high electron mobility and lower electrical noise, is an excellent material for electrochemical studies. Due to its high surface area and electrical conductivity, graphene is well suitable for the good dispersion of metal oxides for electronic/electrochemical applications. Graphene prevents particle agglomeration, whereas the addition of metal oxide prevents layer restacking in graphene. The bulk preparation of graphene via cost-effective and green methods are preferred. The aromatic conjugated π-network along the whole surface is not attained in large scale graphite oxide assisted production due to the defects and functional groups introduced during the hazardous synthetic procedure. Here, less defective graphene is synthesised via ball milling of graphite using metal oxalate as an exfoliating agent for the first time. Calcination of metal oxalate inserted graphite leads to the enormous evolution of gases thereby sliding the graphitic layers, leading to the formation of graphene sheets decorated with ZnO spherical nanoparticles’ bunches. The layer exfoliation and metal oxide incorporation are achieved here via a one-pot synthesis strategy. The use of ZnO/graphene in the selective sensing of 4-nitrophenol is investigated using cyclic voltammetric measurements in the presence of interfering compounds such as glucose, uric acid, ascorbic acid and H2O2.